2011
DOI: 10.1007/s00431-011-1619-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose of intravenous lipids and rate of bacterial clearance in preterm infants with blood stream infections

Abstract: Restriction of the dose of IVLE to 1 g kg(-1) day(-1) in preterm infants with BSI is associated with earlier negative blood cultures and reduced duration of antibiotic therapy but was associated with a lower daily weight increments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…On the other hand, it may also be true that the longer hospital stay was caused by an interference of TPN with rate of bacterial clearance. Shouman et al demonstrated recently that reducing the amount of lipids in TPN was associated with a more rapid sterilization of blood cultures in preterm neonates [21]. However, the design of our study does not allow us to determine any causal relationships.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, it may also be true that the longer hospital stay was caused by an interference of TPN with rate of bacterial clearance. Shouman et al demonstrated recently that reducing the amount of lipids in TPN was associated with a more rapid sterilization of blood cultures in preterm neonates [21]. However, the design of our study does not allow us to determine any causal relationships.…”
Section: Discussionmentioning
confidence: 68%
“…17 Our study reported herein is the first investigation to report an association between increased frequency of lipid emulsion infusion and development of CRBSI. Shouman et al 18 showed bacterial clearance was decreased in animals as well as in preterm infants with bacteremia who received IV lipid emulsion, 19-21 as the reticuloendothelial system may be impaired, [22][23][24] although actual infection risk may not be increased, at least among inpatients during short-term hospitalizations, 22,[25][26][27] with the exception of a study in trauma patients in whom the use of lipid emulsion within the first 10 days of PN was associated with increased infection rate, ICU stay, and total length of hospitalization. 28 Based on the results of our retrospective study, it will be important moving forward to determine in a prospective manner whether the use of soybean oil-based lipid emulsions as a full caloric source are a significant risk for the development of CRSBI and, if so, whether their use solely as a source of essential fatty acids should be considered outside of special circumstances, such as the fluid-overloaded patient, the patient with high serum glucose concentration, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental dose of MOFE, involving a restricted dose of 1 g/kg/d, was associated with significantly rapid clearance of bacteremia and reduction in antibiotic use duration in comparison with a standard dose with increases up to 3.5 g/kg/d. This study proposed that the protective effect of this MOFE is perhaps restricted to lower doses of fat load 41 …”
Section: Ivfes and Sepsismentioning
confidence: 96%